2021
DOI: 10.3390/pr9050818
|View full text |Cite
|
Sign up to set email alerts
|

Partially Reduced Graphene Oxide Modified with Polyacrylonitrile for the Removal of Sm3+ from Water

Abstract: An in situ emulsion polymerization method was used for the synthesis of polyacrylonitrile nanoparticles amino-functionalized partially reduced graphene oxide (PAN-PRGO). After that, hydrolyzed polyacrylonitrile nanoparticles amino-functionalized partially reduced graphene oxide (HPAN-PRGO) nanocomposite was achieved by the modification of nitrile groups of the composite polymer chains to carboxylic groups, aminoethylene diamine, and amidoxime functional groups through partial hydrolysis using a basic solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Various methods including biological treatment, anodic oxidation, oxidation, electrocoagulation, photocatalysis, flocculation/coagulation, adsorption, and membrane filtration were examined and used for the treatment of real textile and dyeing effluents [6][7][8][9][10][11][12][13][14][15][16]. Among the available technologies, adsorption is the most used method due to cost-effectiveness, high efficiency, and easy operation [17]. The adsorption is a procedure based on the transfer of pollutant from aqueous solution to the adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods including biological treatment, anodic oxidation, oxidation, electrocoagulation, photocatalysis, flocculation/coagulation, adsorption, and membrane filtration were examined and used for the treatment of real textile and dyeing effluents [6][7][8][9][10][11][12][13][14][15][16]. Among the available technologies, adsorption is the most used method due to cost-effectiveness, high efficiency, and easy operation [17]. The adsorption is a procedure based on the transfer of pollutant from aqueous solution to the adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme immobilization was reached using different types of materials, including inorganic materials (silica, metal oxides, and clays) [13][14][15], organic materials (natural and synthetic polymers) [16,17], and hybrids (joining organic and inorganic materials) [18]. Among all the materials used, nanomaterials are widely used due to their exceptional properties [19][20][21][22][23][24], such as high surface area, ease of synthesis, low cost, and ease of modification that can enhance the enzymatic activity. Many studies reported the successful immobilization of laccase on the surface of nanomaterials, to improve its stability and catalytic properties, for the removal of the dye from aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue on "Tailoring Polymeric Materials for Specific Applications" gathers recent work on the design and modification of polymeric materials for a variety of applications. These applications include packaging and biodegradable films [1,2], capacitors [3], and water treatment [4][5][6]. In addition, papers which provide a better understanding of specific processes, including chain-end coupling [7], additive manufacturing [8], and surface characterization [9], also lie within this Special Issue.…”
mentioning
confidence: 99%
“…Nitrogen and oxygen containing groups (such as amine, carboxyl, hydroxyl, and cyano groups) are often used in sorption and removal of metal ions in aqueous environments. For example, samarium (III) may be removed using polyacrylonitrile-partially reduced graphene oxide (PAN-PRGO) [4] and chromium (VI) may be removed using polypyrrole doped with magnetic hematite (Fe 3 O 4 )-chitosan nanoparticles (Ppy@magnetic chitosan nanocomposite) [5]. Similarly, removal of organic compounds, such as dyes, from wastewater is also dependent on the attraction between the analyte and absorbent.…”
mentioning
confidence: 99%